FACIES DISTRIBUTION MODELLING AND ANALYSIS OF LOWER BEBULUH GROUP FS2 ÃâÃâ FS3 INTERVAL, X FIELD, KUTAI BASIN, EAST KALIMANTAN - HUMAM FAIQ
Study area is located on X Field, an oil and gas field in Kutai Basin, East Kalimantan Province , which consist an area of ± 1673 km2. The study was conducted on FS2 – FS3 interval of the reservoir, that is a part of Lower Bebuluh Group. Objectives of the study is to determine geological settings specifically lithology, facies, depositional environment, facies distribution pattern, and reservoir potential of the facies for FS2 – FS3 interval. The data used in this study consists of core description reports, wireline logs, and biostratigraphy report from 5 wells, also 2 seismic tops. In order to achieve the objectives, several methods were used, including biostratigraphy data analysis, core data analysis, sequence stratigraphy analysis, electrofacies from wireline logs data, facies’ semivariogram analysis, facies distribution analysis, and facies potential analysis using effective porosity data and gas show. Results of the methods applied are as follows. FS2 – FS3 interval of the reservoir, part of Lower Bebuluh Group, was deposited in Early Miocene on shelf depositional environment, which facies associations are foreshore sand, shoreface sand, shelf ridge, and shelf mud. Variogram curve analysis of the mentioned facies associations, shows the sedimentation with major direction ENESSW and minor direction WNW - ESE. Distribution pattern of shoreface sand and foreshore sand in the southern part of the study area indicates sea level rise, while the distribution of shelf ridge facies in the southern part of the study area indicates influence of the uplift tectonic occurred at the time of deposition. The best reservoir potential belongs to the shelf ridge facies, shown by average effective porosity of 0.15, permeability of 144 mD and gas shows in two wells.